2014
DOI: 10.1371/journal.pone.0101123
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Crystallization Database Links Protein Physico-Chemical Features with Crystallization Mechanisms

Abstract: X-ray crystallography is the predominant method for obtaining atomic-scale information about biological macromolecules. Despite the success of the technique, obtaining well diffracting crystals still critically limits going from protein to structure. In practice, the crystallization process proceeds through knowledge-informed empiricism. Better physico-chemical understanding remains elusive because of the large number of variables involved, hence little guidance is available to systematically identify solution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…A third study looked in detail at the behavior of 182 proteins (also from the NESGC) which were each subject to extensive crystallization screen using 1,536 conditions and developed by the High-Throughput Crystallization Screening Laboratory of the Hauptman Woodward Medical Research Institute [82]. Statistical models were trained on this sample capturing trends driving crystallization.…”
Section: Theoretical and Experimental Evidence For The ‘Sticky Patcmentioning
confidence: 99%
See 2 more Smart Citations
“…A third study looked in detail at the behavior of 182 proteins (also from the NESGC) which were each subject to extensive crystallization screen using 1,536 conditions and developed by the High-Throughput Crystallization Screening Laboratory of the Hauptman Woodward Medical Research Institute [82]. Statistical models were trained on this sample capturing trends driving crystallization.…”
Section: Theoretical and Experimental Evidence For The ‘Sticky Patcmentioning
confidence: 99%
“…In addition, a new correlation was found between crystallization and complementary electrostatic interactions. The study concluded that crystal contacts have ‘specific physico-chemical signature even if they are not biologically functional’ [82]. …”
Section: Theoretical and Experimental Evidence For The ‘Sticky Patcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this tool, as well as MCSG Z-score [54], is limited by its use of data from only one structural genomics center for training, and may thus perform poorly in predicting crystallizability of proteins that differ substantially from those in this relatively small training set. Logistic regression also cannot capture non-monotonic trends [55]. …”
Section: Analysis Of Successful Crystallization Conditionsmentioning
confidence: 99%
“…Fortunately, increasing the number of new structures deposited in public databases [1] enriches our understanding of effective crystallization screens and strategies that can be used with the vast majority of biomolecules that still resist assembly [4]. Yet even elementary structural analyses reveal blind spots in our materials comprehension.…”
Section: Introductionmentioning
confidence: 99%